A Study on the locals' sustainable livelihoods from REDD+ (reducing emissions from deforestation and forest degradation plus) in Cambodia and Myanmar - KIM, Ga-Yeong (KDI School, 2023)
Would it be possible to find balance between conservation and development? REDD+ (Reducing Emissions from Deforestation and forest Degradation, the role of forest conservation, sustainable management of forests and enhancement of forest carbon stocks in developing countries) touches both sides. Here, the development does not mean high technologies and gadgets, rather, it reached out to locals’ livelihood improvement based on enough understanding of their needs and contemplating social, economic, and environmental sustainability. In light of this, REDD+ provides locals with awareness, capacities, capabilities, and opportunities to recognize the alternative income sources and responsible production and consumption of the forest resources. This study examined Korea-Cambodia and Korea-Myanmar REDD+ joint projects which are being implemented from the Korea Forest Service (KFS) by focusing on each human, social, physical, natural, and financial capital to scrutinize influence and link to the locals’ sustainable livelihood. Multi-functional REDD+ activities draw a wide range of carbon and non-carbon benefits for locals in a livelihood dimension. The active interaction between the capitals brings more impact. Among them, this study revealed the key role of social capital in terms of forest governance and its long-term impact on the locals’ livelihood. The legal framework would be a foothold not only for forest protection, sustainable forest management, and also locals’ livelihood improvement. Based on the inclusive institutions and good governance, the density and degree of the social capital will be higher at the community and/or village-based level.
Thesis(Master) -- KDI School: Master of Development Poicy, 2023
Keywords: Deforestation--Cambodia; Deforestation--Burma; Sustainable forestry; Forest management--Environmental aspects